Dielectric and piezoelectric properties of cement-containing piezoelectric composites: Experiments and modeling - Wei Liu; Haoxin Sun; Zhonghua Li; Jianhong Wang; Peikang Bai (Materials & Design, 2023)
In this work, porous honeycomb lead zirconate titanate (PZT) ceramics with one dimensional ordered pore channels were fabricated by the ionotropic gelation of sodium alginate/PZT suspension with SrCl2 solution, then the piezoelectric cement/PZT paste with different mass fraction of PZT component were cast into the porous ceramics to produce cement-containing piezoelectric composites. The influences of PZT mass fraction of piezoelectric cement/PZT paste on the microscopic morphology were studied. The relative permittivity (εr) and longitudinal piezoelectric strain coefficient (d33) of piezoelectric composites were measured and predicted by experiments and modified “unit cell” model respectively, while both results displayed consistency. The composites presented typical electromechanical coupling behavior for the direct and inverse piezoelectric effect of PZT component, when the PZT mass fraction increased to 50 wt%, the cement-containing piezoelectric composites acquired the greatest thickness electromechanical coupling coefficient (Kt) value of 55.69% and acoustic impedance (Z) value of 10.00 MRayls, making it an appropriate candidate material in the structure health monitoring system.